2017
DOI: 10.1136/bmjopen-2016-013097
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation with community-acquired pneumonia among patients with type 2 diabetes: an observational population-based study in Spain from 2004 to 2013

Abstract: ObjectivesTo describe trends in the incidence and outcomes of community-acquired pneumonia (CAP) hospitalisations among patients with or without diabetes in Spain (2004–2013).DesignRetrospective, observational study using the Spanish National Hospital Discharge Database (Conjunto Mínimo Básico de Datos (CMBD)).SettingSpain.ParticipantsWe used national hospital discharge data to select all hospital admissions for CAP.Main outcome measuresIncidence was calculated overall and stratified by diabetes status: type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 35 publications
6
34
0
4
Order By: Relevance
“…Although 83% of interviewees were aware that sepsis is a severe condition requiring urgent medical assistance, they underestimated its mortality, with 50% responding that mortality due to acute myocardial infarction is higher than that due to sepsis. As for vaccination, only 17% of the participants were aware that it reduces the risk of sepsis [9]. This latter finding corroborates those of previous studies which reported that the perception of the severity of pneumonia was associated with receiving vaccination, especially amongst elderly persons [29][30][31].…”
Section: Cap Affects Everyone: Why Do We Not Recognize the Threat?supporting
confidence: 88%
See 1 more Smart Citation
“…Although 83% of interviewees were aware that sepsis is a severe condition requiring urgent medical assistance, they underestimated its mortality, with 50% responding that mortality due to acute myocardial infarction is higher than that due to sepsis. As for vaccination, only 17% of the participants were aware that it reduces the risk of sepsis [9]. This latter finding corroborates those of previous studies which reported that the perception of the severity of pneumonia was associated with receiving vaccination, especially amongst elderly persons [29][30][31].…”
Section: Cap Affects Everyone: Why Do We Not Recognize the Threat?supporting
confidence: 88%
“…The incidence increased in both sexes (from 2.08 to 2.27 in males and from 0.92 to 1.16 in females) and in the older age groups (from 10.06 to 11.00 in the 75-84 year group, and from 2.11 to 25.84 in the ≥85 year group) [7]. Interestingly, two recent studies showed an increase in the incidence of CAP in COPD patients (from 13.44 per 1000 persons/year in 2004-2005 to 16.40 cases in 2012-2013) and in patients with diabetes (from 8.14 per 1000 persons/year in 2004 to 9.23 cases in 2013); COPD and diabetes are both important and frequent comorbidities in CAP patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The lung is not currently considered a potential target organ for diabetes mellitus (DM). However, selected respiratory diseases seem to be more prevalent or more severe in patients with type 1 and type 2 DM . Analogously, both respiratory dysfunction and pathological parenchymal and vascular changes have been variously associated with DM.…”
Section: Introductionmentioning
confidence: 98%
“…However, selected respiratory diseases seem to be more prevalent or more severe in patients with type 1 and type 2 DM. 1,2 Analogously, both respiratory dysfunction and pathological parenchymal and vascular changes have been variously associated with DM. We aim to summarize the main DM-related respiratory problems and to discuss their pathogenetic mechanisms and clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…L'association entre l'incidence de la pneumonie communautaire et le diabète est retrouvée dans la plupart des études (mais pas toutes). Il est également lié à une augmentation de complications de cette pneumonie (bactériémie, empyème, décès) [22][23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Les Infections Respiratoires Bassesunclassified